Adolescent Students and Their Experiences of Dealing with Pregnancy: A Mixed-Method Study in Public Schools from Central Mexico - Erika E Atienzo; Lourdes Campero; Erendira Marin; Guillermo Gonzalez (International Journal of Evaluation and Research in Education (IJERE), 2017)
In impoverished communities in Mexico, most adolescent mothers do not attend school; but typically, they become pregnant once they dropped out. Understanding the experiences of adolescents who have had a pregnancy and continue in school is complicated since few manage to do it. The goal of this study is to describe experiences within the family and school context and plans for the future of a sample of Mexican students who have had a pregnancy. We analyze information from the questionnaires of 68 women and 44 men and interviews to 6 women and 5 men. First intercourse was at age 15 and first pregnancy at 16; 39% of men and 57% of women already have a child; 54% of men and 19% of women work and study simultaneously. Dropping out because of a pregnancy/marriage was reported by 41% of women and 14% of men. The support of family and teachers is crucial to stay in school; but the institution remains indifferent to their plight. The immediate needs easily defeat their aspirations. It is fundamental to acknowledge and notice the experiences of these vulnerable young people in order to design focused strategies promoting their success in adult life.